(untitled) (ENTHYMEMA, 2012)
The child as the embodiment of a new freedom for which the 1800s man aimed. Starting from this matter of fact, from the new value that Rousseau attaches to the child’s education, from Hugo’s creation of the character of Gavroche, “gamin de Paris,” the street rascal that is at the same time independent and rebel, but also innocent and free, we consider here different representations or transgressive figures of the child in the European narrative of the Nineteenth century: from Twain to Sand, from Flaubert to Dickens, from Andersen to Collodi and to his immortal, brat per excellence, Pinocchio.